Gramsci was a Shibboleth - Baier, Walter (International Gramsci Journal, 2023)
During his lifetime, Antonio Gramsci concerned himself little with political events in Austria. Similarly, his posthumously published writings had little influence on the left-of-centre political landscape in that country. Nevertheless, the following interview with Walter Baier, former Chairman of the Austrian Communist Party, examines some of the points of contact and connections between Gramsci and the Austrian Left during the twentieth century. Such points of contact include a) Gramsci’s stay in Vienna between 1923 and 1924 and his critical relationship with Austro-Marxism from a philosophical and political point of view; b) the peripheral influence of Gramsci’s thought on early Eurocommunism in the Austrian Communist Party between 1965 and 1969, which was due above all to the efforts of Franz Marek; c) the Marxist-Leninist reception of Gramsci’s work by the leadership of the Austrian Communist Party which took place at the beginning of the 1980s and was intended as a defensive manoeuvre to counter heterodox interpretations of Marxism within and outside the party; and d) the possible significance of Gramsci for Otto Bauer’s concept of integral Socialism, seen as a revolutionary transformational project for the incipient twenty-first century